Pengaruh Ketersediaan Sarana dan Prasarana Pendidikan terhadap Prestasi Belajar Siswa Kelas X TKR SMK Negeri 2 Siatas Barita Tahun Ajaran 2023/2024 - kristian Simanjuntak (Satya Sastraharing : Jurnal Manajemen, 2024)
The aim of this research is to determine the effect of the availability of infrastructure on the learning achievement of class X TKR students at SMK Negeri 2 Siatas Barita. The method used in this research is an inferential quantitative method. The population was all 127 class X TKR students and a sample of 30 was determined using a non-probability sampling technique, namely purposive sampling. Data was collected using a closed questionnaire with 15 items. The results of data analysis show that there is a positive and significant influence in the availability of educational infrastructure on the learning achievement of class A positive relationship is obtained by the value rxy = 0.553 > rtable(=0.05,n=30) = 0.361, thus it is known that there is a positive relationship between variable > t table(=0.05,dk=n-2=28)= 2.048, thus there is a significant relationship between variable "72.863"+0.130X. b) Regression coefficient of determination test (r2) = 30.5%. 3) Test the hypothesis using the F test to obtain Fcount > Ftable, namely 12.315 > 4.17. Thus Ha is accepted and H0 is rejected.